An Exploratory Study on the Impact of Generative AI on Business Ethics and Governance - Parthasarathy, Suri (Global journal of Business and Integral Security, 2025)
This study gives detailed examination about multifaceted implications towards generative Machine Learning with regards to business ethics and governance, focusing on the ethical, regulatory, privacy, and societal challenges posed by the deployment of these technologies in various industries. Through a qualitative analysis involving diverse stakeholders, the research investigates critical aspects of AI integration, including the management of biases, privacy concerns, intellectual property rights, risk assessment, and stakeholder engagement. The findings reveal that while generative AI offers significant potential for enhancing business efficiency and innovation, it also introduces complex ethical dilemmas and governance challenges. Key issues identified include the need for robust ethical frameworks to mitigate discrimination in AI algorithms, the significance towards safeguarding isolation in an era of pervasive AI applications, and the necessity for clear regulatory guidelines to direct the developing AI outlook. Additionally, the study underscores the crucial part pertaining to transparent AI operations also stakeholder involvement through fostering trust as well as aligning AI deployments with societal values and business ethics.2 The implications of these findings are profound, suggesting that businesses must proactively adapt their strategies to ensure responsible AI integration. This involves not only compliance with current regulations but also active participation in shaping future governance frameworks. Furthermore, organizations are called to prioritize continuous education and workforce development to convey transformative effect pertaining to Machine Learning towards employment as well as workplace dynamics. Overall, this study contributes present dialogue towards responsible use with regards to generative AI and giving precious instinct for businesses, members also researchers aiming to leverage AI technologies while addressing the ethical and social challenges they bring. Keywords Generative AI, Business Ethics, AI Governance, Privacy Concerns, Regulatory Compliance